2014
DOI: 10.1021/jf5018252
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fermented Soybean Suppresses UVB-Induced Skin Inflammation in Hairless Mice via Regulation of the MAPK Signaling Pathway

Abstract: Soybean may be a promising ingredient for regulating UVB-induced inflammatory damage to the skin. We investigated the anti-inflammatory effects of diets supplemented with fermented soybean on UVB-induced skin photodamage and the effectiveness of soybean (S) and fermented soybean (FS) dietary supplementation. To investigate the effects of two major isoflavones-daidzein and genistein-from FS, we used cocultures with keratinocytes and fibroblasts. Genistein treatment strongly inhibited the production of IL-6 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…Although these natural products contain many beneficial bioactive substances, there are some limits in terms of efficacy. Several studies have demonstrated that fermentation of the natural products improved biological activities [23]. Therefore, in order to enhance the beneficial effects of soybean and barley, we increased the activity of β-glucans, daidzein and genistein in barley and soybean by yeast fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Although these natural products contain many beneficial bioactive substances, there are some limits in terms of efficacy. Several studies have demonstrated that fermentation of the natural products improved biological activities [23]. Therefore, in order to enhance the beneficial effects of soybean and barley, we increased the activity of β-glucans, daidzein and genistein in barley and soybean by yeast fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…Genistein and daidzein, which are abundantly present in soy products, are also isofl avones that have diverse biological functions, including anti-allergic, anti-infl ammatory, antioxidant and anti-cancer as well E-mail: hirasaka@nagasaki-u.ac.jp as estrogenic action (13)(14)(15). Our previous study demonstrated that isofl avones prevent TNF-␣-induced myotube atrophy in C2C12 myotubes (16).…”
mentioning
confidence: 99%
“…Our previous study demonstrated that isofl avones prevent TNF-␣-induced myotube atrophy in C2C12 myotubes (16). In addition, it has been reported that the cytoprotective effects of genistein as an anti-infl ammatory agent are also mediated through the suppression of ERK signaling in pancreatic ␤-cells and skin (15,17). However, effects of isofl avones such as genistein and daidzein in counteracting muscle atrophy caused by cancer in vivo are still unknown.…”
mentioning
confidence: 99%
“…During the process of fermentation, the sugar moiety is removed from the compounds genistin and daidzin, converting them into their aglycon forms, genistein, and daidzein. [19]. When soybean extracts (25 g of soybean were extracted 2 times at room temperature with shaking for 48 hours using each solvent) were fed to Sprague-Dawley rats using various solvents (ethanol, n-hexane extract, ethyl acetate), all three extracts caused an increase in estrogen receptor-positive cells to emerge, but only a high-dose ethyl acetate extract group showed an increased amount of collagen in the skin.…”
Section: Soybean Extractsmentioning
confidence: 99%